Hoarding goods in the perspective of the Prophet's hadith, Legal analysis of a term â€œIhtikÃ¢râ€ in Fiqh al-Hadith - Qomarullah, Muhammad (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
This research is a thematic application of hadith fiqhi regarding the law of hoarding goods from the perspective of the Prophet’s hadith. The first step is to determine the equivalent meaning or meaning of words in Arabic. Then, the hadiths that are considered good or credible are in accordance with the science of hadith. Furthermore, conformity with the Qurân and other traditions that are appropriate in meaning. Then, look at the whole meaning of the hadith and the causes that arise from the hadith (asbâb al-wurud). As for the results of the hadiths, what is collected is that it is forbidden to hoard goods when it is related to staple goods due to the consequences of the crisis and the bigger is the emergence of other diseases due to curses from Allah. However, scholars differ on the level of hoarding goods that are carried out in relation to a lot of goods so that they can stay long in the hadith fiqhi